The Multiethnic Slavery Institution through the Eyes of Western Women and 'the real position of women in the religious system of Islam' (Second Edition) - Irene Kamberidou (Media, Religion and Gender in Europe, 2017)
Through the eyes of western women of the 18th and 19th centuries, this paper discusses the Ottoman slavery institution and 'the real position of women in the religious system of Islam' (Garnett 1895: 61).  Focusing on primary sources, first-hand accounts of European women travel writers, authors and journalists in Ottoman territories and principally in Asia Minor (Turkey), this article confirms that all the harem inmates were women of different nations and races: Islamized slaves, liberated slaves and descendants of slaves. Western women, in their intimate contacts with the harem inmates—free and slave—discuss the Ottoman dynasty’s reproductive politics, forced abortion, marriage, divorce, veiling or Muslim women’s attire,  slave rights and social mobility, including requirements for slave liberation. This researcher concludes that the Multiethnic-Multiracial Harem Slavery Institution was the collective segregation, confinement or enslavement of the female gender in one specific space (household/harem), as one collective identity since all the women—slave and free—shared or legally belonged to one man or master: sultan, grand vizier, vizier, pacha, etc. Keywords: slavery, sexual slavery, social mobility, polygyny, eunuchs, children’s harem, seraglio, marriage, divorce, veiling